Analysis of Factors Influencing the Decision to Purchase Yakult Probiotic Drink in Karawang Regency - Mutiara, Mutiara; Citra Savitri; Syifa Pramudita Fadilla (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Public awareness of a healthy lifestyle continues to increase, especially in big cities in Indonesia, thus influencing their consumption patterns, including in choosing health drinks such as Yakult. This fermented milk product is increasingly in demand because of its probiotic content which is considered beneficial for health. However, with the many choices on the market, consumers are becoming more selective and considering various factors such as price, quality, promotion, brand image, and perception of health benefits. PT Yakult Indonesia Persada, as a pioneer of fermented milk products, continues to maintain its reputation by setting competitive prices, maintaining quality, strengthening promotions, and building a positive product image and perception. This study aims to analyze the factors that influence Yakult purchasing decisions in Karawang Regency. The study was conducted quantitatively using a survey method of 140 Yakult consumer respondents. The analysis used the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results showed that price, product quality, promotion, brand image, and perception of health benefits had a positive and significant effect on Yakult purchasing decisions. These findings indicate the importance of a comprehensive strategy in maintaining consumer loyalty.